Monochorionic Diamniotic Vasa Previa Pregnancy: A Medical Student Perspective. (7th April 2021) - Samuel, Joshua M.; Ali, Fatima; Faro, Jonathan; Baum, Jonathan D.
Abstract : Monochorionic diamniotic twins and vasa previa are uncommon. We present a case that was followed from ultrasound diagnosis to delivery.